Metode Inovasi Produk Dalam Meningkatkan Penjualan Produk Dezato Brownies - Dzar Algifari; Zakiyah Zahara; Syamsul Dg. Parani; Suryadi Samudra (STIKes Ibnu Sina Ajibarang, 2024)
In creating a product innovation is needed, in order to differentiate the product from its competitors and what makes the product far superior to other similar products. A company is required to be more innovative in producing a product so that it can attract consumers' interest in buying the product. The method used in this research is descriptive qualitative. This method focuses on problems based on facts carried out by observation, interviews, and studying documents. document. Bogdan and Taylor in Moleong (2010:04) state that qualitative research is